Electronic Service Quality: A Study of Corporate Customer’s Acuity towards e-Banking in India - Brar , Tejinder Pal Singh; Sharma, Dhiraj; Khurmi, Sawtantar Singh (Gyan Management Journal, 2015)
From the past several years Indian banking sector has observed tremendous expansion in terms of electronic banking. Banks offer customers (both retail and corporate customers) number of £-services through variety of channels. When compared to retail customers, more revenue is generated by corporate customers. In the past, service quality factors with respect to corporate customers and£- banking have been moderately studied and especially decision making factors that motivates corporate customers to use electronic channels. This study evaluates £-banking service quality from corporate customer’s view point. The constructs in this study were developed for reliability and validity by using measurement scales from prior studies. In order to confirm factor analysis results, SEM has been employed. The results of study show that service quality have influence on corporate customer’s perceptions. This study has its share of /imitations that also serves as directions for future research.